Efecto sinérgico in vitro del aceite esencial de origanum vulgare orégano con ciprofloxacino frente a E. coli ampicilino-resistente - Contreras Calderón, Sarita Rocío (2017)
Objectives: Identify the in vitro synergistic effect of the Origanum vulgare, “oregano” essential oil with ciprofloxacino, against ampicillin-resistant E. coli, to determine its Minimum Inhibitory Concentration (MIC) and to determine the susceptibility of 50% and 75% essential oil concentrations in synergy with ciprofloxacin against ampicillin-resistant E. coli. Material and Method: The essential oil extraction from Origanum vulgare leaves was carried out using the steam distillation method. Subsequently many separations were done at 5%, 10%, 15%, 20%, 50% and 75% concentrations. The E. coli ampicillin-resistant strains were cultivated and seeded in Petri dishes containing Mueller Hinton Agar. The susceptibility test was then performed using the Kirby and Bauer technique by means of a Whatman No. 4 sterile filter paper discs, which were immersed into each of the essential oil concentrations; which were later placed on the E. coli cultivations. For the control group, Ciprofloxacin and 96% alcohol were used. The plates were incubated at 37 ° C for 24 hours, after which they were read using IMAGEJ software. Results: Significant differences have been found (p <0.05) between the mean inhibition diameters in accordance to the concentration of Origanum vulgare essential oil on the ampicillin-resistant E. coli, which range from 10.62 mm to 22.72mm, with an acceptable variation coefficient. On the other hand, the increase in area of inhibition halos from 1603.02 to 1820.84 mm2 was observed while the concentration of the “oregano” essential oil and ciprofloxacin combination increased from 50 to 75%, in comparison to the control (ciprofloxacin), which had an area of 1244.59 mm2. Conclusions: There exists a synergistic effect between Origanum vulgare "oregano" and ciprofloxacin against ampicillin-resistant E. coli. The minimum inhibitory concentration of the ampicillin-resistant Origanum vulgare essential oil was 5% with an inhibition halo of 11.7 mm. The concentration of essential oil of Origanum vulgare "oregano" to 75% plus ciprofloxacino presented greater inhibition against ampicillin-resistant E. coli